Reconstructing the Second Column in the Cairo Genizah Hexapla Palimpsest: A Proposed Restoration of the Second Column (Secunda) of Origen’s Hexapla as Attested in the Hexapla Fragment T-S 12.182 (Rahlfs 2005) - Kantor, Benjamin (Maarav, 2021)
The second column (Secunda) of Origen’s (185-254 c.z.) Hexapla, which contains Greek transcriptions of a Biblical Hebrew tradition from the Roman period, constitutes the earliest and most extensive evidence for how Biblical Hebrew was pronounced in antiquity. Because most of the Hexapla was lost, however, only highly fragmentary portions of the Secunda remain, totalling not much more than 1,500 words or so. For this reason, any collection of data that can be added to the Secunda corpus, no matter how small, is of immense value to the field of historical Hebrew phonology. On this point, it is noteworthy that the Cambridge Hexapla palimpsest (T-S 12.182), though originally published around the turn of the preceding century, has never been fully utilized with respect to its data on the Secunda. The reason for this is fairly simple, namely that the fragment has a tear going right through the second column. Nevertheless, by carefully measuring the widths of the letters and using comparative Secunda material to reconstruct what is missing, we can actually plausibly reconstruct much of the second column from this fragment. Although much of the reconstru ction is necessarily speculative, there are at least a handful of fairly reliable phonological conclusions that can be drawn from this endeavor. In this way, we can add a bit more data to the Secunda corpus, which will prove valuable for the field of historical Hebrew phonology.